ISTIBDAL WAKAF DALAM PERSPEKTIF FUQAHA DAN RELEVANSINYA TERHADAP UNDANG-UNDANG WAKAF - M. Syukron (Sosio Akademika, 2023)
The conclusion of this study shows that the changing status of benefaction wealth for Islamic jurists is permitted and not permitted, it is because the Islamic jurists use the theoretical framework (Istinbath) of law if Islamic jurists permit the changing status of wealth, so the theoretical framework of law is maslahah, however for Islamic jurists who forbids about the changing status of benefaction wealth, Islamic jurists will hold to hadith narrated by Ibnu Umar.